KARAKTERISASI SANTAN DI SULAWESI UTARA SEBAGAI BAHAN BAKU SANTAN INSTAN - Barasi, Edward; Fatimah, Fety; Mamuaja, Christine F. (Pascasarjana Unsrat, 2014)
Coconut milk is a white viscous liquid obtained by extracting coconut meat well with the addition of water or not. This study aims to investigate the characteristics of pure coconut milk and instant prepared from coconut fruit taken from three regions in North Sulawesi is Sangihe, Bolaang Mongondow and Minahasa, which each region is taken from the coastal areas include testingi.caracteristici pure coconut water content, cream skim while for instant coconut milk protein testing, FFA and viscosity. The results showed no significant effect of sampling at three places in northern Sulawesi on water content, skim cream, proteins, FFA, viscosity, with the largest water content areas at Sangihe 3,24 % and the lowest area at Kalasey and Boltim of 2,98%, the highest value of skim cream at Kalasey 7,08 and the lowest at Sangihe 6,54.Testing result instant coconut milk for protein content showed the highest at Boltim 0,68% and the lowest is to 2,50% area at Sangihe,, the highest FFA at Sangihe and Boltim 0,68% and the lowest in the region Kalasey 0,62%, the largest viscosity at Kalasey 4962,50 cP and the lowest at sangihe of 4875 cP.